DWORKIN, Ronald. Religion without God. - Caldeira, Rodrigo Coppe (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2014)
Resenha: DWORKIN, Ronald. Religion without God. Cambridge: Harvard University Press, 2013. 180p.